A facility location model for marine applications. (2021) - Baskar, A.; Anthony Xavior, M.
Highlights: Proposes a model for marine applications. The model can be suitably modified for other applications also. Weiszfeld algorithm is used to locate the optimal centres, iteratively. Both Great Circle Distance and Ellipsoidal distance metrics are considered. Number of trips from the optimal centre to the data points is taken as the weights. Optimal collection centres, total minimum distance, number of data points attached with each centre are estimated. Abstract: In any facility location problem, some measure of point-to-point distance is a fundamental consideration. The distance metric may be based on a straight line, rectilinear, great circle. Cosine or similar. Though Euclidean distance is used in most of the applications, it may not yield accurate results when the data points are located on Earth surface and are fairly separated. Great Circle Distance is used in such cases assuming the Earth as a perfect sphere, though it is not so. Vincenty's formulae are based on an ellipsoidal model of the Earth and report better results. This paper proposes and analyses a simple model using Vincenty's formulae and compared it with the Haversine formula which is used to calculate the great circle distance. One and two collection points are optimally located for 10 supply points using Weiszfeld iterative algorithm. Though this model can be readily applied for marine applications like oil rigs, drill ships, floating production systems and other drilling barges; they can be used on land also with suitable modifications.